2017
DOI: 10.1016/j.tjog.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Labor induction just after external cephalic version with epidural analgesia at term

Abstract: Considering that a high number of cesarean deliveries can be avoided, induction of labor after ECV with epidural analgesia at term can be considered after being discussed in selected patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Furthermore, it is important to note that none of the studies reported any uterine rupture so it was not possible to compare uterine rupture rate between the two methods, although this catastrophic situation should be always kept into mind [65,66]. In addition, the evidence based for cervical ripening for term induction, as well as caution of the using pharmacological agents or any mechanical methods for induction of labor should be always followed [67][68][69]. It should administer misoprostol cautiously using 25 µg every 4 h as recommended by the WHO and is also the dosage used by most of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to note that none of the studies reported any uterine rupture so it was not possible to compare uterine rupture rate between the two methods, although this catastrophic situation should be always kept into mind [65,66]. In addition, the evidence based for cervical ripening for term induction, as well as caution of the using pharmacological agents or any mechanical methods for induction of labor should be always followed [67][68][69]. It should administer misoprostol cautiously using 25 µg every 4 h as recommended by the WHO and is also the dosage used by most of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there were few parous women in our study, 23 out of 110 women, can be explained by the greater success of the external cephalic version in parous women, which reduces cesarean births because of breech presentation 30,31 …”
Section: Discussionmentioning
confidence: 86%